THE USE OF ANIMATED FILM BASED ON LOCAL WISDOM TO DEVELOP STUDENTS’ IDEAS ON WRITING NARRATIVE TEXT - Dewantari, Arifah Rahmawati; Sari, Ayu Istiana (English Education Department Slamet Riyadi University Surakarta, 2025)
This study was aimed to describing the class condition when the animated film based on local wisdom is implemented in the teaching and learning activity of writing a narrative text and this study also aimed to find out whether the use of animated films based on local wisdom can develop students’ ideas on writing narrative text. The research used Classroom Action Research as the method of study. This research was conducted on May until August. The subject of the research was the students of XI F 7 class of MAN 1 Surakarta in the 2024/2025 academic year. This research used qualitative and quantitative methods to collect the data. The qualitative data was collected through questionnaire, observation, and documentation while the quantitative data was collected through pre-test, post-test 1, and post-test 2. The analysis of the qualitative data using the triangulation method by Miles and Huberman, then the analysis of the quantitative data using the students’ mean score from the test. The result of the research showed that the animated film based on local wisdom can develop students’ ideas on writing narrative texts. The improvement of the students’ writing ability can be proven by the improvement of the students’ mean score in each test. Not just the mean score, but the class condition has also improved. The class condition became more conducive, and the students also became more active and enjoy during the teaching and learning activity. Keywords: Writing Skill, Animated Film, Local Wisdom, Classroom Action Research.